2014
DOI: 10.1016/j.ajpath.2013.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT Imaging of Tumor Angiogenesis

Abstract: Angiogenesis is a hallmark of cancer, and its noninvasive visualization and quantification are key factors for facilitating translational anticancer research. Using four tumor models characterized by different degrees of aggressiveness and angiogenesis, we show that the combination of functional in vivo and anatomical ex vivo X-ray micro-computed tomography (μCT) allows highly accurate quantification of relative blood volume (rBV) and highly detailed three-dimensional analysis of the vascular network in tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 41 publications
(39 reference statements)
6
92
0
Order By: Relevance
“…The relative blood volume (rBV) of these organs was determined based on the ratio between organ and blood enhancement created by the µCT blood pool agent 37,38. For these organs, an average absorption value was estimated from the rBV, the absorption of mixed blood (Table 1) and assuming negligible absorption for unperfused tissue 19.…”
Section: Methodsmentioning
confidence: 99%
“…The relative blood volume (rBV) of these organs was determined based on the ratio between organ and blood enhancement created by the µCT blood pool agent 37,38. For these organs, an average absorption value was estimated from the rBV, the absorption of mixed blood (Table 1) and assuming negligible absorption for unperfused tissue 19.…”
Section: Methodsmentioning
confidence: 99%
“…For example, highly detailed anatomical information obtained at high-resolution by ex vivo microCT has been used to quantitatively analyze the three-dimensional (3D) micromorphology of tumor blood vessels (12) (13). However, a review of the literature revealed no high-resolution ex vivo microCT studies that investigated the dynamic regulation of wound vessels over time.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-computed tomography (CT) and micro-digital subtraction angiography (DSA) with contrast agents have reported in-plane spatial resolutions less than 20 μm in mapping small animal vasculature (Figueiredo et al 2012; Ehling et al 2014). Magnetic resonance (MR) images of vasculature having spatial resolutions as fine as 130 μm in a single direction have also been reported (Zwick et al 2009).…”
Section: Introductionmentioning
confidence: 99%